International obligations and national objectives: Options for plant variety protection in the new millenium: Report on the Regional Workshop in Southern Africa on the Implementation of Article 27.3(b) of the TRIPS agreement, 22-25 March 1999 - Harare, Zimbabwe - Chitsike, L.T.; International Plant Genetic Resources Institute (1999)
The objectives of the Workshop were: to review the regional countries' state of research and breeding activities, biotechnology research capacity, trade in agricultural biological products, formal and informal seed sectors and national IPR relevant for agriculture and PGR; to assess implications for the implementation of TRIPS, particularly Art 27.2(b), for the SADC region; to review the draft sui generis legislative frameworks developed by IPGRI on PGR, and that in Zimbabwe; to get feedback on their possible usefulness as a basis for further developments of similar national legislation; to stimulate discussion among regional stakeholders in the implementing of Art. 27.3(b) of TRIPS, WTO and related IPR regimes; and to identify common regional interests and possible synergies for implementation <//font> <//font><//font>